2018
DOI: 10.1111/josl.12307
|View full text |Cite
|
Sign up to set email alerts
|

Emerging from below the social radar: Incipient evaluation in the North West of England

Abstract: This paper investigates the social meaning of post‐nasal [ɡ]‐presence, a dialectal variant characteristic of North Western varieties of British English that is claimed to have local prestige. Using a matched‐guise approach, this study reveals the absence of a community‐wide norm with respect to how [ŋɡ] clusters are evaluated as well as diachronic change in the level of awareness speakers have of this variable. Older subjects are not sensitive to the dialectal status of [ŋɡ] and as a result do not evaluate it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This phenomenon consists of the conservative realization of etymological ŋɡ as [ŋɡ] rather than [ŋ] in positions where it is not followed by a vowel belonging to the same stem-level domain, so that si[ŋɡ]-er rhymes with fi[ŋɡ]er (Bermúdez-Otero 2011: 2020-2025Bermúdez-Otero & Trousdale 2012: 697-699). In a recent matched-guise experiment, Bailey (2019a) found that Velar Nasal Plus is becoming available to carry social meaning: older speakers exhibit identical responses to [ŋɡ] and [ŋ] guises, but younger speakers show an incipient evaluative distinction. At the same time, sociolinguistic interviews show an increase in the use of [ŋɡ] in apparent time.…”
Section: Granularity Variancementioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon consists of the conservative realization of etymological ŋɡ as [ŋɡ] rather than [ŋ] in positions where it is not followed by a vowel belonging to the same stem-level domain, so that si[ŋɡ]-er rhymes with fi[ŋɡ]er (Bermúdez-Otero 2011: 2020-2025Bermúdez-Otero & Trousdale 2012: 697-699). In a recent matched-guise experiment, Bailey (2019a) found that Velar Nasal Plus is becoming available to carry social meaning: older speakers exhibit identical responses to [ŋɡ] and [ŋ] guises, but younger speakers show an incipient evaluative distinction. At the same time, sociolinguistic interviews show an increase in the use of [ŋɡ] in apparent time.…”
Section: Granularity Variancementioning
confidence: 99%
“…At the same time, sociolinguistic interviews show an increase in the use of [ŋɡ] in apparent time. It transpires, however, that the ongoing incrementation of Velar Nasal Plus is not driven by its incipient indexicality: natural and laboratory data reveal that this incrementation is strictly confined to prepausal position (Bailey 2019b), whereas social evaluation attaches to the [ŋɡ] variant in all contexts, including those in which the variable remains stable (Bailey 2019a).…”
Section: Granularity Variancementioning
confidence: 99%
“…The role of social meaning in driving forward the incrementation of language change has been called into question in cases of sound change specifically (see e.g. Bailey 2019, and Bermúdez-Otero 2020 for a more general discussion of these issues), but it is possible that such causal relationships are more likely in the case of lexical/semantic changes for the reasons discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…This prosodic emphasis in the form of primary accent can also be found in the format tie (line 40/ 41 "tickin' /ticking). Thus the velar serves to construe Amelia as a competent teacher (on the association between formality or professionalism and the velar variant see production and perception work on ing, for example Eckert 2018, p. 157 with reference to Campbell-Kibler 2007Schleef, Flynn and Ramsammy 2015;Barras 2017, andBailey 2019). In the light of the prosodic prominence of some of the velar ing tokens it could be additionally said that the velar draws attention to Amelia's utterances.…”
Section: Alveolar-velar Format Tiesmentioning
confidence: 99%